2015
DOI: 10.1089/lap.2014.0615
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Splenectomy Is a Safe Method in Cases of Extremely Large Spleens

Abstract: Our study supports that the proposal that LS is safe and has numerous advantages, even in the case of massive splenomegaly. Our results were mainly affected by the spleen size and the learning curve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
1
4
0
2
Order By: Relevance
“…8 Although BMI was slightly higher in the LSM group, the good results obtained indicate that the choice of the patient candidate for LS in case of massive splenomegaly also depends on other factors besides BMI. We agree with some Vecchio et al, 15 Tsamalaidze et al, 16 Nyilas et al, 17 stating that a dimensional cut-off of the spleen as the only parameter is insufficient to define the ideal candidate for a laparoscopic approach. A preoperative clinical examination to assess the abdominal "working space" in case of a laparoscopic access is of capital importance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…8 Although BMI was slightly higher in the LSM group, the good results obtained indicate that the choice of the patient candidate for LS in case of massive splenomegaly also depends on other factors besides BMI. We agree with some Vecchio et al, 15 Tsamalaidze et al, 16 Nyilas et al, 17 stating that a dimensional cut-off of the spleen as the only parameter is insufficient to define the ideal candidate for a laparoscopic approach. A preoperative clinical examination to assess the abdominal "working space" in case of a laparoscopic access is of capital importance.…”
Section: Discussionsupporting
confidence: 90%
“…Contrary to the 2008 EAES guidelines on LS, most AA, thanks to the good experience gained in the following years, recommend LS for splenomegaly, regardless of spleen size. 13,22,23 More recently, Nyilas et al 17 and Vecchio et al 15 outlined that LS in massive and giant spleens is still considered a challenging procedure, and it should be reserved for specialized centers, as the most important factor of the successful procedure, besides spleen size, is possibly the experience of the team.…”
Section: Discussionmentioning
confidence: 99%
“… 3 The main limitation of the laparoscopic technique is splenomegaly (a spleen weighing over 500 g), although our previous results showed that laparoscopic splenectomy was not contraindicated, even in the case of extreme splenomegaly (a spleen weighing over 2000 g). 14 Splenomegaly causing technical difficulties is not characteristic of ITP; therefore, this limiting factor is not common either.…”
Section: Discussionmentioning
confidence: 99%
“…A nyitott és a laparoszkópos módszer között nem volt szignifikáns különbség sem a műtéti idő (122 vs. 133 perc, A II. vizsgálatban a 2002. január 1. és 2013. december 31. között végzett 70 laparoszkópos splenectomia eredményeit elemeztük a tanulási periódus (első 20 műtét) szerepe, a hiláris érképletek elzárásának módja (stapler vs. klipp), a léptömeg jelentősége, valamint a specimeneltávolítás módjának szerepe (Endobag þ morcelláció vs. Pfannenstielmetszés) tekintetében [3].…”
Section: Laparoszkópos Splenectomia: Műtéti Előkészítés Sebészi Technikaunclassified